Structure and Functional Characterization of Human Histidine Triad Nucleotide-Binding Protein 1 Mutations Associated with Inherited Axonal Neuropathy with Neuromyotonia. Issue 17 (17th August 2018) - Shah, Rachit M.; Maize, Kimberly M.; West, Harrison T.; Strom, Alexander M.; Finzel, Barry C.; Wagner, Carston R.
Abstract: Inherited peripheral neuropathies are a group of neurodegenerative disorders that clinically affect 1 in 2500 individuals. Recently, genetic mutations in human histidine nucleotide-binding protein 1 (hHint1) have been strongly and most frequently associated with patients suffering from axonal neuropathy with neuromyotonia. However, the correlation between the impact of these mutations on the hHint1 structure, enzymatic activity and in vivo function has remained ambiguous. Here, we provide detailed biochemical characterization of a set of these hHint1 mutations. Our findings indicate that half of the mutations (R37P, G93D and W123*) resulted in a destabilization of the dimeric state and a significant decrease in catalytic activity and HINT1 inhibitor binding affinity. The H112N mutant was found to be dimeric, but devoid of catalytic activity, due to the loss of the catalytically essential histidine; nevertheless, it exhibited high affinity to AMP and a HINT1 inhibitor. In contrast to the active-site mutants, the catalytic activity and dimeric structure of the surface mutants, C84R and G89V, were found to be similar to the wild-type enzyme. Taken together, our results suggest that the pathophysiology of inherited axonal neuropathy with neuromyotonia can be induced by conversion of HINT1 from a homodimer to monomer, by modification of select surface residues or by a significant reduction of the enzyme's catalytic efficiency. Graphical abstract: Unlabelled Image Highlights: Mutations in the enzyme, hHINT1, have been found to be causative for inherited neuropathy and neuromyotonia. The effects of these mutations on hHINT1 structure and catalysis have not been investigated. Several of the mutations resulted in the dimeric protein becoming monomeric, while others significantly reduced catalysis. Either modifications of the solvent accessible surface motif of the homodimeric protein or a loss or significant reduction of the enzyme's catalytic efficiency appears to be associated with inherited axonal neuropathy with neuromyotonia.